Acute response in glycemia and lipemia postprandial after resistance and concurrent training in overweight postmenopausal women - Roberto Carlos Rebolledo-Cobos; Eulalia Amador-Rodero; Yoly Yepes-Charris; Tammy Pulido; Leslie Montealegre; Jimmy Becerra Enriquez; Luz Adriana Sarmiento-Rubiano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: In postmenopausal women, metabolic responses to lipids during postprandial periods following combined exercise training are unknown. Objective: To examine the acute effects of resistance training (RT) and concurrent training (CT) on postprandial lipemia and glycemia in postmenopausal women. Methods: This quasi-experimental, exposure response study, linked 27 women who were randomly divided into three groups and evaluated for anthropometry, physical fitness, and nutrition status. Two experimental groups did a session of different types of physical activities (RT or CT), and a control group did not do any training activities (only aerobic exercise). At 12 hours post-training, in fasting conditions, a hypercaloric nutritional compound equivalent to 50% of the basal metabolic rate (BMR) of each woman was supplied. Pre and post hypercaloric intake, biochemical markers (lipemia and glycemia) were determined and compared with the control group. Results: A reduction in total energy expenditure was observed due to RT and CT training (p<0.005). The changes are associated with decreased total cholesterol and low-density lipoprotein levels in the RT group, as well as decreased triglyceride levels and increased high-density lipoprotein levels in the CT and aerobic exercise groups. Conclusion: RT and CT performed 12 hours before the consumption of the hyper caloric nutritional compound can change postprandial lipid and glucose levels. Acute physical training could influence the reduction of energy expenditure and the improvement of glycaemia and lipemia in postmenopausal women.